Clozapine treatment in schizophrenia, intellectual difficulty and trisomy 5p. Issue 3 (24th August 2020) - Majothi, Naeema; Lee, Hean Yeung; Narayan, Manoj; Butterfield, Victoria
Abstract : There is a considerable paucity of empirical data on the use of clozapine in people with intellectual disability, and to the authors' knowledge these are the first published data on its use in a patient with trisomy 5p and with a diagnosis of schizophrenia. In this case we describe a patient with learning difficulties and a diagnosis of trisomy 5p and schizophrenia that has responded remarkably to clozapine treatment despite numerous additional clinical risk factors.